2021
DOI: 10.3390/ma14195598
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and Electrical Conduction Behaviors of Gd/Cr Codoped Bi3TiNbO9 Aurivillius Phase Ceramic

Abstract: In this work, a kind of Gd/Cr codoped Bi3TiNbO9 Aurivillius phase ceramic with the formula of Bi2.8Gd0.2TiNbO9 + 0.2 wt% Cr2O3 (abbreviated as BGTN−0.2Cr) was prepared by a conventional solid-state reaction route. Microstructures and electrical conduction behaviors of the ceramic were investigated. XRD and SEM detection found that the BGTN−0.2Cr ceramic was crystallized in a pure Bi3TiNbO9 phase and composed of plate-like grains. A uniform element distribution involving Bi, Gd, Ti, Nb, Cr, and O was identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…The editors' research group focused on the preparation, microstructures and electrical behaviors of the modified bismuth layer ferroelectric (BLSFs) ceramics. The authors of [19] studied the microstructures and electrical conduction behaviors of Gd/Cr co-doped Bi 3 TiNbO 9 Aurivillius-phase ceramics. The authors of [20] reported the effects of oxide additives on the phase structures and electrical properties of SrBi 4 Ti 4 O 15 high-temperature piezoelectric ceramics.…”
mentioning
confidence: 99%
“…The editors' research group focused on the preparation, microstructures and electrical behaviors of the modified bismuth layer ferroelectric (BLSFs) ceramics. The authors of [19] studied the microstructures and electrical conduction behaviors of Gd/Cr co-doped Bi 3 TiNbO 9 Aurivillius-phase ceramics. The authors of [20] reported the effects of oxide additives on the phase structures and electrical properties of SrBi 4 Ti 4 O 15 high-temperature piezoelectric ceramics.…”
mentioning
confidence: 99%